'Though an enclosed nun you have not an enclosed mind': Dame Laurentia McLachlan of Stanbrook Abbey. Issue 1 (January 2022) - Truran, Margaret
George Bernard Shaw's insight pays tribute to the remarkable human and spiritual development of Dame Laurentia McLachlan. An enclosed nun since the age of 18, she acquired a breadth of mind and heart that enabled her to touch the lives of many. This article examines afresh her influence as a Benedictine nun and abbess, her pioneering work on Gregorian chant for the liturgy, and the friendship she offered to all she encountered. In the context, light is shed on the history of Stanbrook Abbey, including the ill-founded rumour in the 1880s that Stanbrook intended to leave the English Benedictine Congregation. Belief in prayer and miracles is a recurring theme in Shaw's correspondence with Dame Laurentia; new material about his friendship with the boxing champion, Gene Tunney, and the miraculous response to prayer that saved the life of Tunney's wife, brings further light to bear on this.